A Analysis of Learners' Needs for Energy Literacy as a Reference for E-Module Development at Waterfall Edupark - Damayanti, Fitria Siska; Akhsan, Hamdi; Yusup, Muhamad; Rahman, Nor Farahwahidah Abdul (Indonesian Journal of Education Research (IJoER), 2024)
Purpose of the study: This research aims to analyze the needs of students in learning physics related to energy literacy by utilizing the potential of waterfalls as a reference for developing e-modules in Edupark. Methodology: The methodology of this study is survey- quantitative descriptive research. Data collection through questionnaires given to respondents using google form. The research location is at Senior High School 1 Prabumulih, Senior High School 04 Ogan Komering Ulu, Senior High School 1 Merapi Timur, Senior High School 6 Prabumulih, Senior High School 1 Makarti Jaya, Senior High School 1 Bayung Lencir, Senior High School 10 Palembang, Senior High School 2 Palembang, Senior High School 1 Unggulan Muara Enim. Main Findings: The findings of this study tentang Do you think physics is a difficult subject to learn percentage 64%, Have you ever visited a waterfall before percentage 50,1%, Have you ever been taught energy related concepts on waterfalls percentage 31,5%, Have you ever been taught using E-Modules related to waterfall eduparks percentage 51%, Have you ever heard of hydropower before percentage 87,1%, Do you agree that hydropower can provide more stable energy than other renewable energy sources percentage 89,1%. Novelty/Originality of this study: The novelty of this study lies in the e-module associated with the waterfall edupark towards students' energy literacy. The findings can provide new insights in the context of education and researchers to develop appropriate innovations to improve e-modules.